The Impact of Implementation of the Canadian Regulatory Requirements on the Quality of Natural Health Products: The Glucosamine Case - Ali Aghazadeh-Habashi; John Duke; Fakhreddin Jamali (Frontiers Media S.A., 2014)
ABSTRACT - Purpose. We investigated whether the recent implementation of the regulatory requirements for the entry to the Canadian market of natural products has resulted in improved quality of the available glucosamine products. Methods. Eleven available products, of which 8 had been tested in 2002 (7 had contained substantially lower than the label claim of the active ingredient), and a European pharmaceutical grade tablet were assayed for their glucosamine content. The potassium and sodium contents of the products were also tested. Results. Nine of the 11 Canadian products and the European tablet had more than 91% of the label claim of the active ingredient, hence, met the criterion. Two products contained 71 and 78% label claim. The electrolyte contents were very variable but constituted only a small fraction of the daily requirements. Conclusion. Most tested glucosamine products passed the Health Canada requirements. This improvement is likely due to the publicity regarding the low quality of the products in the past and also a result, at least in part, of the introduction of the new regulatory requirements.  The sub-standard quality of a few tested products is still of concern. This  article  is  open  to  POST-PUBLICATION  REVIEW.  Registered  readers  (see  "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.